Penyusunan Anggaran Belanja Daerah Dengan Pendekatan Ad-Daruriyyat Al-Khams/Maqasid As-Syariah: Studi Kasus APBD Kabupaten Bogor Tahun 2011 - Deni Lubis (AL-MUZARA'AH, 2013)
The welfare of people in a certain area can be observed from the income and budget allocation. If the income of the local government will be high then the local community is prosperous citizens and vice versa. Budget allocation should be considered its effectiveness whether or not it is allocated for the welfare of the local citizens. According to As-Syatibi, human being have five besic needs or called as ad- daruriyyat al – khams. They are to keep or maintan the faith (religion), to maintan life, intellect, descent, and property. The concept of five basic needs is taken from the purpose of shariah revelation ar called as Maqasid As- Shari'ah. From these five basic needs it has to be observed whether a needs is included dharuriyat (primary), hajiyyat (secondary), or tahsiniyyat (luxuries). In the budget process, the budget allocation for maintenance of religion should be the highest priority, followed by life needs, maintenance of life, maintenance of descent, and the property maintenance. Consecutively this is consistent with the Government’s vision, which is to realize Bogor as pios self dependent and culture, rich city. This vision must be reflected Bogor district budget allocation. In general, Bogor district budget has been allocated to the five basic needs, but in terms of allocation still not in line with the concept of ad- daruriyyat al – khams. It is because some of the budget posts have been covered by central government, such as religious activity post by Ministry of Religious Affairs, law enforcement post by Ministry of Law and Human Rights, and security post by police and army.